The wicked deep - Ernshaw, Shea (New York : Simon Pulse, 2018)
Three sisters, drowned as witches in Sparrow, Oregon, in the 1800s, return each summer for revenge but Penny, seventeen, is determined to stop them to save the boy she loves.
Keywords: Love -- Fiction; Revenge -- Fiction; Supernatural -- Fiction; Witches -- Fiction; Sisters -- Fiction; Coasts -- Fiction; Oregon -- Fiction